Factors influencing the surgical outcome of spontaneous intracerebral haematoma - Raihan, Md Zahid; Rashid, MH; Syed, MA; Sarkar, MH (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):245-9. The abstract of this article is available on the PubMed website